Uit genade alleen? Herbesinning oor die Romeinebrief deur Suid-Afrikaanse teoloë - Lombard, H. A. (Hervormde teologiese studies, 1991)
Through faith, from begimiing to end? Rethinking the Letter to the Romans by South African theologians As material for and reflection on religious issues by Christians, the letter to the Romans used to be a document of fundamental importance. It ought to be ap plauded that in 1989 a contribution to this letter was made by South Africans in their own context, with a view to meeting their situation and needs. The eleven contributions represent the authors’ religious sense of responsbility and social sensitivity. They also display the nature and content of their hermeneutical vanta"e points and their competence in exegetical procedures. Apart from the merit and indisputable value of these contributions, cognizance should also be taken of deficiencies with regard to methodological precision and competence in some of the articles. A salient deficiency is the lack of cognizance of the work of South African theologians and discussions with them. This is to be regretted.